The role of the cash basis in limited purpose financial reporting - Lotter, Willem Adriaan (College of Accounting, 2017)
The strictly regulated environment within which corporate accounting practice evolves, has traditionally paid little attention to the owner-managed corporation and the speciﬁc information needs of its owners. The literature, as well as recent corporate law amendments, though, hints strongly that owner-managed entities have different ﬁnancial reporting priorities than their publicly accountable counterparts. This difference in ﬁnancial reporting priorities calls for rethinking at the most fundamental level of ﬁnancial reporting, i.e. accrual versus cash-basis financial reporting. This implies that the debate about the extent of sophistication that should be built into the accrual-basis model can only be conducted sensibly after the primary debate of accrual versus cash-basis, is resolved satisfactorily. The question as to whether measurement and recognition criteria within an accrual-basis model should be relaxed is therefore part of the secondary debate. The basic research question relates to the usefulness to owner-managers of cash-basis accounting compared to accrual-basis accounting. This thesis reports on the responses of 243 practising members of the South African Institute of Professional Accountants (SAIPA) regarding owner-manager needs and preferences regarding ﬁnancial accounting recording and reporting practices. Semi- structured interviews were conducted with owner-managers to verify the understanding of the practitioners regarding owner-manager needs and preferences. The results showed and explained an apparent paradox: owner-managers have a strong cash focus in the way they understand and use ﬁnancial information, but nevertheless prefer accrual-basis annual ﬁnancial statements. The unresolved challenge identiﬁed by this study is to design a ﬁnancial report which could better bridge the gap between accrual-basis and cash-basis accounting than the conventional statement of cash flow.